2015
DOI: 10.1186/s13063-015-1062-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recruitment methods for a trial targeting childhood obesity: Families for Health randomised controlled trial

Abstract: BackgroundRecruitment to trials evaluating the effectiveness of childhood obesity management interventions is challenging. We report our experience of recruitment to the Families for Health study, a randomised controlled trial evaluating the effectiveness of a family-based community programme for children aged 6–11 years, versus usual care. We evaluated the effectiveness of active recruitment (contacting eligible families directly) versus passive recruitment (informing the community through flyers, public even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 16 publications
(19 reference statements)
3
28
0
Order By: Relevance
“…In agreement with findings from other similar programs, we also found that those who were self-referred had better program attendance [19, 21]. However, none of our hypothesized child and parent factors were shown to mediate these relationships.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with findings from other similar programs, we also found that those who were self-referred had better program attendance [19, 21]. However, none of our hypothesized child and parent factors were shown to mediate these relationships.…”
Section: Discussionsupporting
confidence: 91%
“…Although, we found that professionally referred parents had higher levels of concern for their child’s weight status and its consequences on child health, these families attended on average 1.5 sessions less than those who were self-referred. Plausible explanations that align with previous studies [19, 21] include that self-referred parents were seeking support and were therefore more committed to the program and for professionally referred families, their enrolment in the program was not based on personal motivations (and/or their readiness to change) and/or their decision to attend did not involve their children, subsequently limiting their ongoing commitment to program attendance [16]. Another possible explanation based on the historical management of child obesity (i.e.…”
Section: Discussionsupporting
confidence: 85%
“…We aimed to recruit 40 families from each of three sites, using active and passive recruitment methods. 12 Active recruitment methods were via letters to families with an eligible child identified by the National Child Measurement Programme and by referrals from healthcare professionals, including dietitians and general practitioners (GPs). Passive recruitment methods were via the local media (newspapers and radio); flyers and posters at schools, GP surgeries and other community venues and attending public events.…”
Section: Methodsmentioning
confidence: 99%
“…These factors are further complicated by the challenges of obtaining parental consent for the child to participate [8] , [9] , [10] . Previous studies have shown that parental willingness to allow their children to participate in clinical trials is variable based on numerous factors, including: recruitment strategies used [11] , [12] , age of the child [11] , [13] , race [14] , socioeconomic status [15] , type of study or the perceived risk [15] , [16] , and health status of the child [13] . Fewer data exist that describe specific operational tactics and interventions that have the most impact on parents' perceptions of clinical trials.…”
Section: Introductionmentioning
confidence: 99%